2022
DOI: 10.1159/000526909
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Survival Results of Peritoneal Dialysis Patients Suffering from COVID-19 in Turkey: A Multicenter National Study

Abstract: Background: We aimed to study the characteristics of peritoneal dialysis (PD) patients with Coronavirus disease-19 (COVID-19), determine the short-term mortality and other medical complications, and delineate the factors associated with COVID-19 outcome. Methods: In this multicenter national study, we included PD patients with confirmed COVID-19 from 27 centers. The baseline demographic, clinical, laboratory, and radiological data and outcomes at the end of the first month were recorded. Results: We enrolled 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…The most common symptoms were cough, followed by fever, myalgia and sore throat, similar to the symptoms in the general population. The rates of hospitalisation (16.2%) and mortality (3.8%) were lower than those in previous studies which reported a hospitalisation rate of 33-58% and a mortality rate of 23-52% [11][12][13][14]18,27,28 in dialysis patients with COVID-19, perhaps owing to the lower severity of the Omicron variant and the protection from vaccines. 29,30 However, these rates are still much higher than those reported in the general population (reported hospitalisation rate of approximately 2% and mortality rate of 0.1%), 8,31,32 confirming the poor outcome of COVID-19 in the PD population.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The most common symptoms were cough, followed by fever, myalgia and sore throat, similar to the symptoms in the general population. The rates of hospitalisation (16.2%) and mortality (3.8%) were lower than those in previous studies which reported a hospitalisation rate of 33-58% and a mortality rate of 23-52% [11][12][13][14]18,27,28 in dialysis patients with COVID-19, perhaps owing to the lower severity of the Omicron variant and the protection from vaccines. 29,30 However, these rates are still much higher than those reported in the general population (reported hospitalisation rate of approximately 2% and mortality rate of 0.1%), 8,31,32 confirming the poor outcome of COVID-19 in the PD population.…”
Section: Discussioncontrasting
confidence: 64%
“…Although the infection rates among patients of all ages were similar, the rates of hospitalisation, severe disease and mortality were significantly higher in older patients. The higher risk of poor outcome in older people with COVID-19 has been reported in previous studies, 4,12,14 re-emphasising the need to pay more attention to this population during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our study showed the results of short-term fatality and risk factors, which were similar to previous reports from other countries. Previous studies showed that the fatality rates from COVID-19 infection in patients with dialysis were 20% to 30% [ 8 10 , 14 , 16 , 28 , 32 34 ]. Advanced age, multiple comorbid conditions, diabetes, frailty, and the need for ventilation were risk factors related to death [ 4 , 8 10 , 28 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%